Incidents in the life of a slave girl authoritative text, contexts, criticism - Jacobs, Harriet A. 1818-1896 (A Norton critical edition, 2019)
"Harriet Jacobs's 1861 autobiography was the first written narrative by a female slave in America. Using the pseudonym Linda, Jacobs recounts the horrors of her life as a slave and a mother. She documents the physical and sexual abuse she went through prior to her escape from slavery and gaining freedom for herself and two children. The "Contexts" section provides a selection of public statements written by prominent abolitionists, including Harriet Jacobs, on the cruelty of slavery. A selection of correspondence between Harriet Jacobs and her fellow abolitionists is also included. The "Criticism" selection examines a variety of topics, ranging from the form of the text to discussions on oral tradition, activism, the intersection of race and gender, and print culture. A Chronology and Selected Bibliography are also included."...Provided by publisher